PERBANDINGAN TINGKAT KESEGARAN JASMANI SISWA KELAS X IPS SMA NEGERI 1 RENGAT BARAT DAN SISWA KELAS X FARMASI SMK KESEHATAN HAR-KAUSYAR KECAMATAN RENGAT BARAT KABUPATEN INDRAGIRI HULU - Deci Aprilita; Zainur Zainur; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem in this research is satiety during learning, so the learning process of exercise in class X IPS SMA Negeri Rengat Barat and class X Pharmacy at SMK Kesehatan Han-Kausyar is not optimal, which is not always done. Don't get better. The purpose of this study was to determine whether there is a comparison between the physical fitness of the two schools for these students. The population in this research consisted of male students of class X IPS and male students of class X pharmacy, a total of 55 persons. The sampling technique used cluster random sampling where the sampling was performed in the area with a sample of 15 students from West Rengat Barat High School and 12 Han-Kausyar Health Vocational Schools. The tools used in this study were the 60-meter walk test, 60-second pull-up, 60-second sit-up, vertical jump, 1200-meter run. The data obtained was analyzed using the independent